2022
DOI: 10.1111/jocd.15006
|View full text |Cite
|
Sign up to set email alerts
|

Eyebrow lifting with barbed threads: A simple, safe, and effective ambulatory procedure

Abstract: Introduction: Changes in brow positioning are one of the first facial aging signs. A more beautiful and younger look can be achieved by repositioning the tissues involved in brow descent and sagging eyelids. Methods:We report the outcome of eyebrow thread lifting in a series of patients who came to our clinic to improve their gaze. Response to treatment was assessed at 6-and 12-months using FACE-Q ™ upperlids and eyebrow/forehead scales.Results: A total of 38 patients with mild-to-moderate brow ptosis or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…From the perspective of safety profile, thread lift procedures have a great safety profile except for minor complications. Santorelli et al 14 reported hematoma, minor extrusion in two patients of 38 patients. Rezaee Khiabanloo et al 15 reported tumefaction in one patient and ecchymosis in four patients in their eight brow lift patients.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…From the perspective of safety profile, thread lift procedures have a great safety profile except for minor complications. Santorelli et al 14 reported hematoma, minor extrusion in two patients of 38 patients. Rezaee Khiabanloo et al 15 reported tumefaction in one patient and ecchymosis in four patients in their eight brow lift patients.…”
Section: Discussionmentioning
confidence: 97%
“…From the perspective of safety profile, thread lift procedures have a great safety profile except for minor complications. Santorelli et al 14 However, they noted that there might be significant advantages if thread lift sutures were combined with an open procedure. 4 In the literature, authors evaluating the efficacy of threads for midface lift reported that the results were moderate and durability was not sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
Thread-lifting plastic surgery techniques are favored due to their relative safety, ease of procedure and effectiveness, and low risk of side effects. 1,2 Recently, absorbable threads have been developed as an alternative to non-absorbable cogged threads, which are associated with rejection and are not conducive to adjustment. 3 These absorbable threads mechanically lift the skin immediately after implantation, 4 and do so for approximately 6 months, when the threads degrade through hydrolysis.
…”
mentioning
confidence: 99%